The Effect of Environmental Performance, Environmental Management System, and Institutional Ownership on Carbon Emission Disclosure with Media Exposure as a Moderating Variable - Yanto, Heri; Hajawiyah, Ain; Baroroh, Niswah; Kardiyem, Kardiyem; Abd Rahman, Nur Hayati; Meliana, Lulus Nona (International Journal of Energy Economics and Policy, 2025)
This study examines the effects of environmental performance, environmental management systems, and institutional ownership on carbon emission disclosure. It also investigates the moderating role of media exposure in these relationships. The research population comprises non-financial sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. A purposive sampling method was employed, resulting in 174 units of analysis. Secondary data were collected using documentation techniques. The study applies descriptive and inferential analyses, utilizing panel data regression and Moderated regression analysis (MRA) with the EViews software. The results show that environmental performance does not significantly affect carbon emission disclosure. Environmental management systems positively influence carbon emission disclosure, while institutional ownership has a negative impact. Additionally, media exposure does not moderate the relationships between environmental performance, environmental management systems, and institutional ownership with carbon emission disclosure. This study differs from previous research in that it uses specific indicators for environmental performance and includes media exposure as a moderating variable.